How Do Nursing Students Perceive Moral Distress? An Interpretative Phenomenological Study - Chiara Gandossi; Elvira Luana De Brasi; Debora Rosa; Sara Maffioli; Sara Zappa; Giulia Villa; Duilio Fiorenzo Manara (MDPI AG, 2023)
Background: Research shows that the longer nurses care for terminally ill patients, the greater they experience moral distress. The same applies to nursing students. This study aims to analyze episodes of moral distress experienced by nursing students during end-of-life care of onco-hematologic patients in hospital settings. Methods: This study was conducted in the interpretative paradigm using a hermeneutic phenomenological approach and data were analyzed following the principles of the Interpretative Phenomenological Analysis. Results: Seventeen participants were included in the study. The research team identified eight themes: causes of moral distress; factors that worsen or influence the experience of moral distress; feelings and emotions in morally distressing events; morally distressing events and consultation; strategies to cope with moral distress; recovering from morally distressing events; end-of-life accompaniment; internship clinical training, and nursing curriculum. Conclusions: Moral distress is often related to poor communication or lack of communication between health care professionals and patients or relatives and to the inability to satisfy patients' last needs and wants. Further studies are necessary to examine the quantitative dimension of moral distress in nursing students. Students frequently experience moral distress in the onco-hematological setting.